1997
DOI: 10.1111/j.1365-2990.1997.tb01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve regeneration through nerve guides seeded with adult Schwann cells

Abstract: This study tested the usefulness of Schwann cells in the repair of a severed nerve with a biosynthetic bridge or guide. Reinforced collagen nerve guides were used to bridge an 18 mm gap in the sciatic nerve of 21 young adult rats. The animals were divided into three groups and the guides were filled with: (i) more than 0.5 x 10(6) cultured syngeneic adult Schwann cells (group L, n = 12); (ii) less than 0.5 x 10(6) Schwann cells (Group S, n = 6); and (iii) phosphate buffered saline (control, n = 3). Schwann cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(43 citation statements)
references
References 42 publications
0
39
0
4
Order By: Relevance
“…By 52 weeks, a regenerate inside a cell-seeded tube reached a conduction velocity 60 % of normal, a noteworthy result considering that it had formed across a gap as long as 18 mm in the rat sciatic nerve (Ansselin et al 1997). Furthermore, a very significant increase in critical axon elongation of SCseeded over unseeded experimental groups, amounting to ΔL ≥ 7.4, was observed (Table 6.1).…”
Section: Schwann Cell Addition To the Tubulated Gapmentioning
confidence: 89%
See 1 more Smart Citation
“…By 52 weeks, a regenerate inside a cell-seeded tube reached a conduction velocity 60 % of normal, a noteworthy result considering that it had formed across a gap as long as 18 mm in the rat sciatic nerve (Ansselin et al 1997). Furthermore, a very significant increase in critical axon elongation of SCseeded over unseeded experimental groups, amounting to ΔL ≥ 7.4, was observed (Table 6.1).…”
Section: Schwann Cell Addition To the Tubulated Gapmentioning
confidence: 89%
“…Schwann cells have been exogenously supplied in the gap between the tubulated nerve stumps in a number of cases with very good results, as discussed in Chap. 6 (Guénard et al 1992;Kim et al 1994;Son and Thompson 1995;Ansselin et al 1997). Even in these cases, however, neither the tube type was selected to take advantage of its role as a nondiffusible regulator nor was a nondiffusible tube filling with regenerative activity employed.…”
Section: Toward Simple Protocols For Synthesis Of the Entire Organ Imentioning
confidence: 99%
“…This experimental method involving the use of transplanted Schwann cells in addition to axonal frameworks [36,37,38] avoids many of the drawbacks associated with surgical repair and can be accomplished using one of three different delivery systems: (1) a hollow tube filled with cells may be placed in the injured site; (2) the cells can be set in hydrogel prior to being packed into the tube lumen; or (3) the aforementioned cell-laden hydrogel can be loaded into a tube that contains a supportive scaffolding [39]. The first method of delivery is the most commonly studied; however, significant loss of cells is an important potential drawback [35,40,41,42]. The second [37,38] and third [36] techniques are associated with both better results as well as higher levels of cost and technical complexity.…”
Section: Sources Of Schwann Cellsmentioning
confidence: 99%
“…Although autogenous nerve grafting is still considered the best current method for bridging peripheral nerve lesions with substance defect (Terzis et al 1997), several other grafting conduits (i.e., biological or synthetic tubes) have been studied experimentally for nerve repair (Lundborg et al 1981;Glasby et al 1986;Jimming et al 1986;Brunelli et al 1987;Rich et al 1989;Mackinnon and Dellon 1990;Chen et al 1994;Ansselin et al 1997). Previous studies showed that a new surgical procedure, named muscle-vein-combined grafting technique, could give very good results even for the repair of longdistance nerve defects (Brunelli et al 1993;Battiston et al 2000a,b).…”
Section: Introductionmentioning
confidence: 99%